INFLUENCE FINANCIAL KNOWLEDGE,FINANCIAL SELF-EFFICACY, AND LOCUS OF CONTROL TO ISLAMIC FINANCIAL BEHAVIORON GENERATION Z IN DKI JAKARTA - Muhammad Reza Pahlavi; Gusniarti; Mitra Sami Gultom (Universitas Efarina, 2022)
This research aims to determine the effectFinancial Knowledge, Financial Self- Efficacy, AndLocus of Controleither partially or simultaneously towardsIslamic Financial Behavioramong Generation Z in DKI Jakarta. This type of research is quantitative with a causality approach. The method used in sampling ispurposive sampling. Partial test results show that the variablefinancial knowledgepositive and significant effect onIslamic financial behavior,financial self-efficacy positive and significant effect onIslamic financial behavior, Andlocus of controlpositive and significant effect onIslamic financial behavior. The results of this study also show thatfinancial knowledge,financial self- efficacy, Andlocus of control simultaneously has a positive and significant effect onIslamic financial behavior.